2010
DOI: 10.1158/0008-5472.can-10-1313
|View full text |Cite
|
Sign up to set email alerts
|

hsa-miR-191 Is a Candidate Oncogene Target for Hepatocellular Carcinoma Therapy

Abstract: Hepatocellular carcinoma (HCC) is generally a fatal disease due to a paucity of effective treatment options. The identification of oncogenic microRNAs that exert pleiotropic effects in HCC cells may offer new therapeutic targets. In this study, we have identified the human microRNA miR-191 as a potential target for HCC therapy. Inhibition of miR-191 decreased cell proliferation and induced apoptosis in vitro and significantly reduced tumor masses in vivo in an orthotopic xenograft mouse model of HCC. Additiona… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
112
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 145 publications
(125 citation statements)
references
References 47 publications
12
112
0
1
Order By: Relevance
“…The evidence of cancer xenograft models in our study has already been shown, but studies to date have shown only changes in tumor size when cells were transfected by miR-338-3p and control vector, and then injected to produce the tumor model. Such studies were also performed for prostate cancer (37), hepatocellular carcinoma (38), and pancreatic cancer (39). These results also confirmed the tumor-suppressive role of miR-338-3p in gastric cancer.…”
Section: Discussionsupporting
confidence: 70%
“…The evidence of cancer xenograft models in our study has already been shown, but studies to date have shown only changes in tumor size when cells were transfected by miR-338-3p and control vector, and then injected to produce the tumor model. Such studies were also performed for prostate cancer (37), hepatocellular carcinoma (38), and pancreatic cancer (39). These results also confirmed the tumor-suppressive role of miR-338-3p in gastric cancer.…”
Section: Discussionsupporting
confidence: 70%
“…Elyakim et al (42) reported that miR-191-5p inhibition has great potential in the treatment of hepatocellular carcinoma patients. In addition, miR-191-5p is a potential target in treating radiation-resistant lung cancer according to the study by Liu and Huang (43).…”
Section: Discussionmentioning
confidence: 99%
“…1A) were amplified in breast cancer compared with normal breast tissues. miR-191 has been validated to be amplified and is viewed as a candidate oncogenic miRNA in liver (38), stomach (39), and pancreas (40). LOH comprises not only monosomy, caused by loss of 1 allele, but also homozygous disomy and homozygous polysomies, caused by the concurrent loss of 1 allele and endomultiplication of the other allele (41).…”
Section: Discussionmentioning
confidence: 99%